The role of bud protection and bark density in frost resistance of savanna trees - De Antonio, A. C. [UNESP]; Scalon, M. C.; Rossatto, D. R. [UNESP] (Wiley-Blackwell, 2019)
Frost events occur with a significant frequency in savannas of the Southern Hemisphere, especially in the Cerrados of Brazil. One of the main strategies to deal with such events is to invest in thick and dense bark, which can insulate internal branch tissues and protect buds, essential to ensure resprouting if frost damage causes plant canopy die-back. Such strategies may be fundamental to determine the persistence of savanna species in regions where low temperatures and frost events are recurrent. Here we describe bud protection and bark strategies of 53 woody species growing in typical savanna vegetation of central Brazil. In addition, we used an experimental approach exposing branches to 0 degrees C to measure temperature variation in internal branch tissue and test its relationship to bud protection and bark properties. We found that the majority of species (69%) showed medium to high bud protection against extreme temperatures; however, the degree of bud protection was not clearly related to bark properties, such as bark thickness and density. Bark density is a fundamental trait in determining protection against low temperatures (0 degrees C), since species with low bark density showed lower temperature variation in their internal branch tissues, independently of the bud protection degree. Bark properties and bud protection are two different (albeit related) strategies for the protection and persistence of savanna trees under extreme environmental temperatures and can explain ecological observations related to savanna tree responses after frost events.
Keywords: bark density; bark thickness; bud protection; Cerrado; low temperature